IMPLEMENTASI KEBIJAKAN SERTIFIKASI GURU DALAM RANGKA MENINGKATKAN KINERJA GURU UPTD SD NEGERI 122345 - Simanjuntak, Melvin; Daniel Syaputra Silaen; Junita Hutagalung; Mona Laras Bungaria. S; Herlina Harefa; Sonia Girsang; Adelove Damanik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze 1) How is the implementation of the performance of certified teachers in the learning process at UPTD SD Negeri 122345?; 2) What are the factors that hinder the low performance of certified teachers in UPTD SD Negeri 122345? 3) What efforts have been made by school principals to overcome obstacles in the performance of certified teachers? This study uses a qualitative method at UPTD SD Negeri 122345. The results of the research are 1) The performance of certified teachers is good, both in terms of discipline, namely coming on time, leaving at the specified time, it's just that some older teachers do not understand how to use technology. 2) Factors that hinder the low performance of certified teachers, namely: Low ability (knowledge) and skills in terms of understanding technology, Lack of motivation from, Lack of control or supervision by the principal over various teacher activities in the school, lack of training in making learning tools and not mastering information technology. 3) The efforts made by the principal to the expected performance of certified teachers are to firmly reprimand and sanction certified teachers who are lazy to teach, hold training on making learning tools and must master information technology and conduct continuous evaluation.